Effects of weight-bearing dance aerobics on lower limb muscle morphology, strength and functional fitness in older women - Peng,Xiaoying; Zhou,Tang; Wu,Hua; Li,Yiyan; Liu,Jiajia; Huang,Huan; He,Changshuang; Guo,Shaoyu; Huan,Muyang; Shi,Lei; Chen,Peijie; Quan,Minghui (PeerJ, 2024)
Objective To investigate the effects of 12-week weight-bearing dance aerobics (WBDA) on muscle morphology, strength and functional fitness in older women. Methods This controlled study recruited 37 female participants (66.31y ± 3.83) and divided them into intervention and control groups according to willingness. The intervention group received 90-min WBDA thrice a week for 12 weeks, while the control group maintained normal activities. The groups were then compared by measuring muscle thickness, fiber length and pennation angle by ultrasound, muscle strength using an isokinetic multi-joint module and functional fitness, such as 2-min step test, 30-s chair stand, chair sit-and-reach, TUG and single-legged closed-eyed standing test. The morphology, strength, and functional fitness were compared using ANCOVA or Mann-Whitney U test to study the effects of 12 weeks WBDA. Results Among all recruited participants, 33 completed all tests. After 12 weeks, the thickness of the vastus intermedius (F = 17.85, P < 0.01) and quadriceps (F = 15.62, P < 0.01) was significantly increased in the intervention group compared to the control group, along with a significant increase in the torque/weight of the knee flexor muscles (F = 4.47, P = 0.04). Similarly, the intervention group revealed a significant improvement in the single-legged closed-eyed standing test (z = −2.16, P = 0.03) compared to the control group. Conclusion The study concluded that compared to the non-exercising control group, 12-week WBDA was shown to thicken vastus intermedius, increase muscle strength, and improve physical function in older women. In addition, this study provides a reference exercise program for older women.
Keywords: Weight-bearing exercise; Dance aerobics; Muscle loss; Functional fitness